DEVELOPMENT STAGES AND CONFLICTS OF PEDAGOGICAL EDUCATION IN TURKESTAN IN 1920-1930 - Mamatkulova Makhfuza Kozimovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article analyzes the stages of formation and development of pedagogical education from a scientific and historical perspective against the backdrop of fundamental changes in the socio-political and cultural life of Uzbekistan (Turkestan) in the 1920s and 30s. The author highlights the ideologization of the education system with the change of state administration, campaigns to eliminate illiteracy, the abolition of old-fashioned schools and madrasas, and the issues of training teaching staff for new Soviet schools. Special attention is also paid to the role of Soviet educational policy in destroying national values in the region and replacing it with a policy of Russification.